Effect of oxoanions on oxidant decay, bromate and brominated disinfection by-product formation during chlorination in the presence of copper corrosion products. (1st December 2019) - Fang, Chao; Ding, Shunke; Gai, Shibo; Xiao, Rong; Wu, Yinan; Geng, Bing; Chu, Wenhai
Abstract: The present study investigated the effect of oxoanions on catalytic behaviour of copper corrosion products (CCPs) during chlorination of bromide-containing waters. Three types of oxoanions (carbonate, sulphate, and phosphate) and four types of CCPs (Cu 2+, Cu(OH)2, Cu2 O, and CuO) were involved in investigation and the effect of oxoanions concentration was also examined. The result indicated that carbonate and sulphate slightly inhibited oxidant decay in the presence of CCPs, but the formation of brominated disinfection by-products (Br-DBPs) remained largely unchanged. In contrast, the presence of phosphate (0.2–1 mM) almost eliminated the catalytic effect of Cu 2+ . For CCP solids (i.e. Cu(OH)2, Cu2 O, and CuO), phosphate preferentially inhibited the formation of bromate rather than Br-DBPs. Despite the catalysis by CCP solids was reduced to some extent, the oxidant decay rate and bromate and Br-DBP formation were still significantly higher than blank groups, even at high phosphate concentration. By testing different addition scheme (simultaneous/sequential addition), it was proposed that phosphate was a strong competitor for hypohalites, rapidly destroying CCPs-hypohalites complexes on some adsorption sites. However, there were some specific sites that can only be adsorbed by hypohalites, leading to the incomplete inhibition of phosphate. Finally, the inhibition effect of phosphate on CCPs catalysis was tested in real water matrix. For Cu 2+, higher reduction of bromate and Br-DBPs was found in raw water rather than filtered water, while converse pattern was true for Cu(OH)2 and Cu2 O, and this discrepancy can be ascribed to the difference in catalytic mechanism between Cu 2+ and CCP solids. Graphical abstract: Image 1 Highlights: CCPs-catalysed oxidant decay and Br-DBP formation was strongly inhibited by phosphate. Carbonate and sulphate exhibited less effect on catalytic behaviour of CCPs than phosphate. Phosphate preferentially suppressed the formation of bromate rather than that of Br-DBPs. Competitive mechanism between oxoanions and hypohalites was proposed. The inhibition effect of phosphate was verified in real waters.